Determination of Ebselen by HPLC: Validation and application of the method - (:unkn) unknown (VIEWEG, 2004)
Ebselen is an organo-selenium, highly hydrophobic compound that exhibits glutathion peroxidase-like activity. It is now in phase III trials in Japan for investigating its effect on ischemic stroke. We have developed an HPLC method for the determination of Ebselen at ambient temperature and applied it to a patented tablet formulation. The mobile phase composition, detection wavelength and chromatographic conditions were optimized. The optimum conditions are a Waters, C-18, (25 cm x 4.6 mm, 5 mum) column, 1% acetic acid: methanol: propanol (40:50: 10) (v/v) as the mobile phase at a flow rate of 0.7 mL min(-1) and detection at 254 nm (internal standard: benzanilide). The method was validated and calibration curves were constructed depended on the ratios of Ebselen to benzanilide peak areas. The concentration range for Ebselen was 0.82-11.71 mug mL(-1), y = 0.4021x + 0.0145 (r(2) = 0.9993). Limit of quantification (LOQ) and limit of detection (LOD) were determined as 1.49 mug mL(-1) and 0.45 mug mL(-1) respectively, based on the blank signal and standard deviation of the peak areas of the minimum concentration of Ebselen. Recovery of Ebselen was found to be 98.70 +/- 0.75% for 30 mg of tablet powder and 97.43 +/- 0.78% for the 30 mg tablet form. The RSD was found to be 1.27% for 10 replicate injections of 50 muL. The ruggedness of the method was investigated by carrying out the some procedure on different days. There was no significant difference between 2 and 7 days time periods. The HPLC method is compared to a spectrophotometric method.
Keywords: column liquid chromatography; Ebselen; method validation; hydrophobic drugs; COMPOUND